Internalisasi Nilai-Nilai Pendidikan Islam dalam Menghadapi Dampak Penggunaan Gadget terhadap Psikologi Anak di Gampong Peurada - Hamdi Multazam; Loeziana Uce (Jurnal Ilmiah Guru Madrasah, 2025)
The use of gadgets by children has become an inseparable phenomenon in daily life in the digital era. This study aims to analyze the impact of gadget usage habits on children's psychological aspects, including emotional development, social skills, and behavior. This research employs a qualitative method through literature review and observation of children aged 5–12 years. The findings indicate that excessive gadget use can lead to concentration disorders, increased aggressive behavior, and a decline in social interaction and empathy. On the other hand, guided and appropriate gadget use can enhance children's cognitive abilities and creativity. Therefore, parental involvement and time management in gadget use are crucial factors in minimizing its negative psychological effects on children